Procurement strategies of Neolithic colouring materials: Territoriality and networks from 6th to 5th millennia BCE in North-Western Mediterranean. (July 2016) - Pradeau, Jean-Victor; Binder, Didier; Vérati, Chrystèle; Lardeaux, Jean-Marc; Dubernet, Stéphan; Lefrais, Yannick; Regert, Martine
Abstract: In the N.-W. Mediterranean area, the development of the Neolithic way of life during the 6th millennium cal. BCE is related to the spread of sailing pioneer groups. In the course of the 5th millennium cal. BCE, more stable agro-pastoral settlements expand their hold on the hinterland and exchange networks increase in complexity (obsidian, flints, clastic rocks). Although previous research showed high variability in the N.W. Mediterranean Neolithic diffusion modalities, the place of colouring materials, naturally abundant in this area, has received scant attention despite their technical and symbolic value. With the aim of assessing the place of these materials in the initial Neolithic package and within the development of the neolithisation process, we investigated series of more than 2000 blocks of colouring materials from two key-sites (Pendimoun and Giribaldi) recently excavated by one of us (DB), with dates ranging from 5750 to 3650 cal. BCE. This study was implemented by geological surveys that allowed the establishment of cartography of putative sources of raw colouring materials and the determination of their nature and composition. Combining petrographic examination and physico-chemical-characterisation (SEM-EDS, XRD), we determined a wide range of raw materials: psammitic sandstone, allochthonous and parallochthonous bauxite, oolithic ironstone, oxidised marcasite and ferruginous rocks derived from weathered glauconitic limestones. Comparing archaeological series to this frame of reference highlights two contrasting economic systems: one based on exploitation of local sources from the Early to the Middle Neolithic, the other one founded on a dual use of both close geomaterials and exogenous rocks during Middle Neolithic. Highlights: A colouring materials economic frame of reference was established for Provence area. The economy of colouring rocks is analysed from 5750 to 3650 cal. BCE, through several cultural complexes. Various colouring rocks are exploited as Neolithic pioneers set in N.-W. Mediterranean area. Some of the rocks were collected more than 80 km from the site. Two contrasting economic patterns have been highlighted.